DEPRECIATION AND THE FINANCING OF REPLACEMENTS. - Mason, Perry (The Accounting Review, 1935)
Abstract The belief that it is the principal if not the sole purpose of depreciation accounting to provide for the financing of the replacement of plant and equipment with units of the same type or capacity when the individual items have to be retired from service is widely accepted and frequently expressed. This opinion is now seldom found in technical accounting publications but it is still frequently present in general business, engineering and legal literature. The early publications on bookkeeping and accounting are largely manuals of technical procedure with little to indicate the underlying philosophy or principles. In 1764 John Smeaton, an English engineer, worked out an elaborate schedule for the operation of a canal which provided for an annual income which would cover the "common annual expenses" and would provide a fund accumulated at compound interest by equal annual installments which would "preserve the work to perpetuity" by financing the replacement of parts of the canal as they wore out, although he indicated in a comment at the end of the schedule that the increased trade which could be expected would take care of these irregular repairs without the creation of such a fund out of income.